Human leukocyte antigen and idiosyncratic adverse drug reactions. Issue 1 (February 2017) - Usui, Toru; Naisbitt, Dean J.
Abstract: A clinical association between a specific human leukocyte antigen (HLA) allele and idiosyncratic adverse drug reactions (IADRs) is a strong indication that IADRs are mediated by the adaptive immune system. For example, it is well-established that HLA-B*15:02 and HLA-B*57:01 are associated with carbamazepine-induced Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) and abacavir-induced hypersensitivity/flucloxacillin-induced liver injury, respectively. Drug-specific T-cells whose response is restricted by specific HLA risk alleles have been detected from IADR patients, also suggesting an adaptive immune pathogenesis. T-cells from carbamazepine SJS/TEN patients are activated by direct pharmacological interaction between carbamazepine and HLA-B*15:02 expressed on antigen presenting cells (APCs). Abacavir-specific, HLA-B*57:01-restricted T-cells are activated by APCs presenting peptides which are only displayed by the HLA molecule when abacavir is bound during peptide loading. Finally, HLA-B*57:01-restricted activation of T-cells from patients with flucloxacillin-induced liver injury is dependent on processing of drug protein adducts. Based on these observations, it is now possible to utilize blood from healthy drug-naïve volunteers to study the priming of naïve T-cells to drugs. Future development of these methodologies may lead to the development of assays that predict intrinsic immunogenicity of drugs and chemicals at the preclinical stage of drug development. Graphical abstract: